If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -3m = 13 Solving 5 + -3m = 13 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3m = 13 + -5 Combine like terms: 5 + -5 = 0 0 + -3m = 13 + -5 -3m = 13 + -5 Combine like terms: 13 + -5 = 8 -3m = 8 Divide each side by '-3'. m = -2.666666667 Simplifying m = -2.666666667
| x-4+25/5 | | -8+2m=-6(m+2) | | 3x(x-5)-2(x-2)(x+2)=(x+4)(x+1)-16 | | x=1000-20y-50z | | -2y-6=3y+19 | | 4x+9y=23 | | .1x+2y+5z=100 | | F(x)=2x-11 | | 8x+1.5xy=300 | | 5x+4=-2x-5 | | 6a/17a | | f(x)=3x^3-4x^2-27x+36 | | x+1.5x=300 | | 7x=0+2x | | 5i=0 | | -1.27-46d=7.93 | | 5f-160/9 | | 5/7u=3 | | -10=-2+1.5d | | 1/2(-2) | | -2+16=-5v+3v | | (5x-2)(x^5-4x+1)= | | 4x-2x-9x+5y= | | 7y=4.9 | | F(x)=x(x-8)-33 | | 7y=4+9 | | x/3+5 | | 2c-12= | | g+14=5g-16 | | -4u+6u=6-4 | | 25+7x=15x | | (x^-5/6)^6 |